The concept of rationality in Andrew Gleeson’s antitheodicy - Wiertz, Oliver J. (International journal of philosophy and theology, 2017)
Under an ‘antitheodicy’, I understand any attempt to show the principal impossibility of a morally respectable and rationally convincing theoretical answer to the theoretical problem of evil which is understood as a problem of consistency and rational coherence between propositions. In this paper, I will analyse the concept of rationality which is presupposed at least in some strands of antitheodicy. A. Gleeson’s ‘A frightening love. Recasting the Problem of Evil’ presupposes a dichotomy between an engaged-existential and a detached-impersonal kind of philosophical thinking which are respectively characterized by a stress on authenticity and the acknowledgement of particularity and contingency in the first case and by precision, logic, provability and an instrumental understanding of rationality in the second case. The second kind of reasoning which underlies all theodicies is inapt for dealing adequately with the real problem of evil. I try to show that the dichotomy of impersonal objective and existentially subjective kinds of philosophy is not a contradictory one but leaves out a broad field in-between which can be characterized as ‘informal reasoning’ and which allows a morally sensitive answer to the theoretical problem of evil which is not isolated from the ‘real’ problem of evil.